STRENGTHENING STUDENTS' INDEPENDENT CHARACTER THROUGH THE IMPLEMENTATION OF THE LEARNING BY DOING METHOD IN SCOUT EXTRACURRICULAR ACTIVITIES IN ELEMENTARY SCHOOL - Banjar Mustika Hening; Ine Kusuma Aryani; Y. Suyitno; Subuh Anggoro (SOSIOEDUKASI, 2026)
Strengthening students' independent character in elementary schools is important, but its implementation still needs to be optimized through scouting extracurricular activities. This study aims to critically analyze the strengthening of students' independent character through the implementation of the learning by doing method in scouting extracurricular activities in elementary schools. The qualitative research method with a case study design at SDN Tayem 01, Cilacap. The research subjects included 2 scout instructors, 6 students, and the principal. Data were collected through interviews, observations, and documentation. Data were analyzed using an interactive model, namely data condensation, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources and techniques. The results of the study indicate that the application of learning by doing through real practice, meaningful learning experiences, striving through real actions, problem-solving based on experience, as well as interaction and collaboration in Scouting activities can encourage the development of students' independent character gradually. Students become more confident, less dependent on others, and complete assignments responsibly without having to be reminded. It is concluded that learning by doing in scouting extracurricular activities is effective in forming the independent character of elementary school students. Teachers and all related parties need to optimize the application of the learning-by-doing method in extracurricular activities to strengthen students' independent character in a sustainable manner